HUBUNGAN SELF EFFICACY DAN SELF-REGULATED LEARNING DENGAN TINGKAT KECEMASAN DALAM MENGHADAPI UJIAN STUDENT ORAL CASE ANALYSIS PADA MAHASISWA FK UPNVJ PADA TAHUN AKADEMIK 2023/2024 - Nadya Shahnaz Shafia Azhari (2024)
Medical education use Problem Based Learning concept known as tutorial learning to obtain prospective doctors with the 7 Indonesian Doctor Competency Standards. Student Oral Case Analysis (SOCA) is a form of assessment which aims to measure knowledge, analytical skills and clinical reasoning including integrated clinical cases. Despite the goals of SOCA, there is an increase in anxiety among medical students which gives bad impact on physical and psychological functioning. Self efficacy and self-regulated learning are thought to be factors that influence anxiety in facing SOCA. This study aims to determine the correlation between self efficacy and self-regulated learning with level of anxiety regarding SOCA in medical students. This research is an analytical observational study using cross sectional approach. The research uses primary data with Spearman correlation analysis. The results shows p-value number between self efficacy and the level of anxiety regarding SOCA is 0.000 and the p-value between self-regulated learning and the level of anxiety regarding SOCA is 0.817. It can be concluded that there is a significant negative relationship between self efficacy and anxiety levels regarding SOCA. There is no significant relationship between self-regulated learning and anxiety levels regarding SOCA. The higher the student's self efficacy, the lower the level of anxiety regarding SOCA.